Impact of emergency physician-staffed ambulances on preoperative time course and survival among injured patients requiring emergency surgery or transarterial embolization: A retrospective cohort study at a community emergency department in Japan - Yuko Ono; Yudai Iwasaki; Takaki Hirano; Katsuhiko Hashimoto; Takeyasu Kakamu; Shigeaki Inoue; Joji Kotani; Kazuaki Shinohara (PLoS ONE, 2021)
Injured patients requiring definitive intervention, such as surgery or transarterial embolization (TAE), are an extremely time-sensitive population. The effect of an emergency physician (EP) patient care delivery system in this important trauma subset remains unclear. We aimed to clarify whether the preoperative time course and mortality among injured patients differ between ambulances staffed by EPs and those staffed by emergency life-saving technicians (ELST). This was a retrospective cohort study at a community emergency department (ED) in Japan. We included all injured patients requiring emergency surgery or TAE who were transported directly from the ED to the operating room from January 2002 to December 2019. The primary exposure was dispatch of an EP-staffed ambulance to the prehospital scene. The primary outcome measures were preoperative time course including prehospital length of stay (LOS), ED LOS, and total time to definitive intervention. The other outcome of interest was in-hospital mortality. One-to-one propensity score matching was performed to compare these outcomes between the groups. Of the 1,020 eligible patients, 353 (34.6%) were transported to the ED by an EP-staffed ambulance. In the propensity score-matched analysis with 295 pairs, the EP group showed a significant increase in median prehospital LOS (71.0 min vs. 41.0 min, P < 0.001) and total time to definitive intervention (189.0 min vs. 177.0 min, P = 0.002) in comparison with the ELST group. Conversely, ED LOS was significantly shorter in the EP group than in the ELST group (120.0 min vs. 131.0 min, P = 0.043). There was no significant difference in mortality between the two groups (8.8% vs.9.8%, P = 0.671). At a community hospital in Japan, EP-staffed ambulances were found to be associated with prolonged prehospital time, delay in definitive treatment, and did not improve survival among injured patients needing definitive hemostatic procedures compared with ELST-staffed ambulances.